Gestión de recursos humanos y calidad del servicio al cliente en la empresa Praxair S.A.C. - Cueva Villanueva, Santos (2011)
The present research is aimed at diagnosing the practices of Human Resource Management and Quality Customer Service in the company under study. Posed the following problem: How best practices in human resource management improve the quality of customer service in the company PRAXAIR SAC?, For it suggests the hypothesis: "The application of good practices in Human Resources Management contribute significantly to improving the quality of customer service in the company PRAXAIR SAC ". The purpose of this research study is the company PRAXAIR SAC The population consists of a hand the workers, as well as customers. For data collection were used: surveys, interviews, direct observation. With the investigation reached the following conclusion: The process of human resource management are integrated and dynamic system, in spite of this, the company many decisions affecting staff are taken on a largely disjointed and so informal. Little can serve as a training program, if recruitment and selection are inadequate, or if after being trained employees quit by low wages or failing to equity incentives.